Standards for permanent tooth emergence in Czech children - Romana Šindelářová; Lucie Žáková; Zdeněk Broukal (BMC, 2017)
Abstract Background The aim of this study is to develop a population-specific reference for permanent tooth emergence among 4-15 years old Czech Republic children. The reference derived from this sample population are essential for pediatric dental diagnostics, orthodontic treatment planning, as well as anthropological and forensic applications. Methods In this cross-sectional epidemiological survey, dental examinations of 1,370 Czech children (696 girls (50,8%) and 674 boys (49,2%), whose parents or legal guardians all signed informed consent forms) from 11 elementary schools and kindergartens were performed in the classroom. During the examination, previously emerged permanent teeth (other than third molars), the child's age and gender were recorded. A tooth is defined as having erupted when at least any part of the crown penetrates the gingiva, and is clinically seen in the oral cavity. A logistic regression model was used to calculate the median emergence age per tooth for both genders and the total sample. The data was statistically processed (using IBM SPSS Statistics 23) and carried out at a deviation level of 0.05. The statistical significance of the differences in the emergence of permanent teeth (contralateral, intermaxillary, inter-gender differences) was evaluated by the McNemar test. Results No statistically significant differences were observed in the emergence times between right and left sides. In addition, mandibular teeth emerged earlier than the corresponding maxillary ones (with the exception of the first and second premolars). Permanent teeth were found to emerge sooner in girls. Furthermore, the greatest inter-gender difference was observed in maxillary canines. Conclusions The new data reported can now be used as standards when assessing permanent tooth emergence of Czech children.